Renal Transplantation with Simultaneous Aortoiliac Reconstruction Using a Polytetrafluoroethylene Vascular Graft for Severe Atherosclerosis - Go Anan; Koji Nanmoku; Masaki Shimbo; Masahiko Nagahama; Takaaki Kimura; Yasunaru Sakuma; Fumiyasu Endo; Yasuhiro Komatsu; Kazunori Hattori; Takashi Yagisawa (Case Reports in Transplantation)
Studies on aortoiliac reconstruction for severe atherosclerosis with renal transplantation are limited. Here, we report a rare experience of the simultaneous reconstruction of the external iliac artery caused by severe atherosclerosis with polytetrafluoroethylene vascular graft and renal transplantation in a 55-year-old female; she was unable to undergo standard renal artery anastomosis to the right external iliac artery because of severe atherosclerosis, which would result in complete occlusion. Next, we directly anastomosed the donor renal artery to the polytetrafluoroethylene graft. After transplantation, delayed graft function occurred; therefore, the patient had to undergo hemodialysis. On day 7 after transplantation, her creatine level started to decrease. She was discharged from the hospital on the 14th day after transplantation. After 1 month, her serum creatinine level reduced to 1.12 mg/dL. After 3 years of transplantation, her serum creatinine level was 1.2 mg/dL. The simultaneous implantation of the polytetrafluoroethylene graft and renal transplantation was feasible as well as safe, with no infectious complications and stable renal function noted on long time follow-up. Although our case was rare, it emphasizes the need for transplant surgeons to gain surgical skills for vascular surgery using vascular grafts.